Sosialisasi Pengembangan Ayam KUB (Kampung Unggul-Balitan) Dalam Upaya Mempermudah Pengadaan Daging Ayam Kampung di Daerah Wisata Sembalun Lombok Timur - Budi Indarsih; Ni Ketut Dewi Haryani; I Nyoman Sukartha Jaya; I Gede Nano Septian; Mohammad Hasil Tamzil (Universitas Mataram, 2025)
A community extension program on the dissemination of KUB chicken was carried out in Sembalun Village, East Lombok, with the aim of increasing local awareness of KUB chickens as a sustainable source of native chicken meat and as a potential contributor to tourism development. The program was held at the Piona Farm Eco-Edu Tourism Center and involved lectures, group discussions, and technical demonstrations on poultry management. The activity was well-received, as reflected by active community participation, high enthusiasm, and numerous inquiries, particularly concerning poultry health and opportunities for diversifying livestock production. The results indicated improvements in knowledge, awareness, and initial commitment of the community to develop poultry enterprises based on local resources. This initiative underscores the strategic role of livestock extension in supporting food self-sufficiency, strengthening rural economies, and enhancing the potential of culinary tourism in Sembalun.